Answer:
41/6
Step-by-step explanation:
Take the root of both sides and solve.
If h moves the graph left or right,
![y= \frac{1}{x+h}](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B1%7D%7Bx%2Bh%7D%20)
(moves left)
![y= \frac{1}{x-h}](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B1%7D%7Bx-h%7D%20)
(moves right)
If a vertical stretch by a factor of |h|, then
![y = \frac{h}{x}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7Bh%7D%7Bx%7D%20)
If h moves the graph up or down,
![y= \frac{1}{x} +h](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B1%7D%7Bx%7D%20%2Bh)
(moves up)
![y= \frac{1}{x} -h](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B1%7D%7Bx%7D%20-h)
(moves down)
![y= \frac{1}{-hx}](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B1%7D%7B-hx%7D%20)
and h = 1
Answer:125
Step-by-step explanation:hope this help
Pretty sure the answer is D:
Because the equation is in the format y=mx+c (c being the y intercept), we know that the y intercept (or where the line will cross the y axis) will be -9.
B also says -9 but we have to be careful because it states that the x axis is -9 rather than the y axis.
Hope that helped you understand.